2017
DOI: 10.3390/su9122304
|View full text |Cite
|
Sign up to set email alerts
|

CSR Disclosure in Polish-Listed Companies in the Light of Directive 2014/95/EU Requirements: Empirical Evidence

Abstract: On 15 December 2016, new non-financial reporting requirements were implemented in the Polish Accounting Act (PAA) which would be enforced from 1 January 2017. This act resulted from the transposition of Directive 2014/95/EU. New requirements oblige certain groups of entities to disclose non-financial information on environmental, social and employee-related matters, respect for human rights, anti-corruption and bribery matters. The purpose of this paper is two-fold. Firstly, this study analyses the new non-fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
59
1
11

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(87 citation statements)
references
References 39 publications
(51 reference statements)
8
59
1
11
Order By: Relevance
“…The results were inconsistent with the research conducted by Branco and Rodrigues [4] in Portugal. Moreover, the content analysis and a rating scale conducted by Matuszak and Różańska [57] on the basis of 150 Polish companies also confirmed these results. Szczepankiewicz and Mućko [58] stated that "mining and energy companies are faced with the challenge of responding to the growing demand for energy, while simultaneously improving air quality, reducing emissions and tackling climate change and shrinking resources".…”
Section: Discussionsupporting
confidence: 53%
“…The results were inconsistent with the research conducted by Branco and Rodrigues [4] in Portugal. Moreover, the content analysis and a rating scale conducted by Matuszak and Różańska [57] on the basis of 150 Polish companies also confirmed these results. Szczepankiewicz and Mućko [58] stated that "mining and energy companies are faced with the challenge of responding to the growing demand for energy, while simultaneously improving air quality, reducing emissions and tackling climate change and shrinking resources".…”
Section: Discussionsupporting
confidence: 53%
“…These researchers confirmed many important scientific contributions [13][14][15][16][17][18], despite other studies having found a significant correlation between quantitative and qualitative measures of SRQ [19]. Researchers have consistently developed different metrics and instruments to measure SRQ, most of which are based on a compounded approach and on content analysis [12,[19][20][21][22][23][24][25]. According to Helfaya et al [12] (p. 18) quantity can be considered a secondary factor of quality because the most important determinants concern the content of the reports and are related to aspects of sustainability reporting such as information type, adoption of guidelines, and inclusion of quantitative or financial measures of social and/or environmental performance.…”
Section: Introductionmentioning
confidence: 63%
“…This understanding of CSR is questioned by the intervention of the state, union agreements, implicit cultural and institutional norms and other non-explicit behaviours influencing the CSR engagement. Matten and Moon [56,57] approach to CSR recognizes that not all CSR is entirely voluntary; especially in the European Union (EU), some parts of CSR are highly integrated in institutional norms, values and (regulated) legislation (more e.g., [58]). The differences in perception of CSR between Western and CEE countries may result from the differences in the institutional framework indicated by Ericson [59] and Kornai [60], concerning mainly the socialist legacy and economic development level and growth rate [61].…”
Section: Csp-cfp Relation In Banks and Its Determinants In Ceecmentioning
confidence: 99%